Estrogen Alters the Synaptic Distribution of Phospho-GluN2B in the Dorsolateral Prefrontal Cortex While Promoting Working Memory in Aged Rhesus Monkeys. (1st December 2018) - Hara, Yuko; Crimins, Johanna L.; Puri, Rishi; Wang, Athena C.J.; Motley, Sarah E.; Yuk, Frank; Ramos, Tiffany M.; Janssen, William G.M.; Rapp, Peter R.; Morrison, John H.
Graphical abstract: Highlights: The majority of monkey dlPFC dendritic spines contain pGluN2B regardless of age or estradiol treatment. In young monkeys, estradiol reduces the percentage of cytoplasmic pGluN2B. In aged monkeys, estradiol increases cytoplasmic pGluN2B and reduces synaptic pGluN2B. In aged monkeys, lower synaptic and higher cytoplasmic pGluN2B distribution correlates with better working memory scores. Abstract: Age- and menopause-related deficits in working memory can be partially restored with estradiol replacement in women and female nonhuman primates. Working memory is a cognitive function reliant on persistent firing of dorsolateral prefrontal cortex (dlPFC) neurons that requires the activation of GluN2B-containing glutamate NMDA receptors. We tested the hypothesis that the distribution of phospho-Tyr1472-GluN2B (pGluN2B), a predominant form of GluN2B seen at the synapse, is sensitive to aging or estradiol treatment and coupled to working memory performance. First, ovariectomized young and aged rhesus monkeys ( Macaca mulatta ) received long-term cyclic vehicle (V) or estradiol (E) treatment and were tested on the delayed response (DR) test of working memory. Then, serial section electron microscopic immunocytochemistry was performed to quantitatively assess the subcellular distribution of pGluN2B. While the densities of pGluN2B immunogold particles in dlPFC dendritic spines were not different across age or treatment groups, the percentage of gold particles located within the synaptic compartment was significantly lower in aged-E monkeys compared to young-E and aged-V monkeys. On the other hand, the percentage of pGluN2B gold particles in the spine cytoplasm was decreased with E treatment in young, but increased with E in aged monkeys. In aged monkeys, DR average accuracy inversely correlated with the percentage of synaptic pGluN2B, while it positively correlated with the percentage of cytoplasmic pGluN2B. Together, E replacement may promote cognitive health in aged monkeys, in part, by decreasing the relative representation of synaptic pGluN2B and potentially protecting the dlPFC from calcium toxicity.